Quantification of hypochlorite in water using the nutritional food additive pyridoxamine - Kaarsholm, Kamilla M. S.; Kokkoli, Argyro; Keliri, Eleni; Mines, Paul D.; Antoniou, Maria G.; Jakobsen, Mogens Havsteen; Andersen, Henrik R. (My University, 2021)
Chlorine is a widely used disinfectant and oxidant used for an array of municipal and industrial applications, including potable water, swimming pools, and cleaning of membranes. The most popular method to verify the concentration of free chlorine is the colorimetric method based on DPD (N, N-diethyl-p-phenylenediamine), which is fast and reasonably cheap, but DPD and its product are potentially toxic. Therefore, a novel, environmentally friendly colorimetric method for the quantification of residual chlorine based on the food additive pyridoxamine (4-(aminomethyl)-5-(hydroxymethyl)-2-methylpyridin-3-ol) was investigated. Pyridoxamine is a B6 vitamin with an absorption maximum at 324 nm and fluorescence emission at 396 nm. Pyridoxamine reacts rapidly and selectively with free chlorine, resulting in a linear decrease both in absorbance and in emission, giving therefore calibration curves with a negative slope. The pyridoxamine method was successfully applied for the quantification of free chlorine from 0.2 to 250 mg/L. Using 1 cm cuvettes, the limit of quantification was 0.12 mg Cl2 /L. The pyridoxamine and the DPD methods were applied to actual environmental samples, and the deviation between results was between 4% and 9%. While pyridoxamine does not react with chloramine, quantification of monochloramine was possible when iodide was added, but the reaction is unfavourably slow.
Keywords: Free chlorine; Quantification method; Absorbance; Fluorescence; Pyridoxamine